Osteoradionecrosis of the Exenterated Orbit. (3rd March 2014) - Peter, Neena M.; Laitt, Roger; Leatherbarrow, Brian
Abstract: Osteoradionecrosis (ORN) occurs in an estimated 2% of head and neck-irradiated patients. It is seen most commonly in the mandible with other reported sites including the maxilla, temporal bone, clavicle, and vertebrae. It is defined as an area of exposed devitalised irradiated bone, with failure to heal during a period of at least 3 months, in the absence of local neoplastic disease. We report 2 cases of ORN following postoperative radiotherapy given to patients who had undergone an orbital exenteration. ORN can develop spontaneously in one-third of cases, although in the majority of patients, it is induced by secondary trauma. Radiotherapy induces an endarteritis in the small blood vessels of bone, thus favouring the generation of small thrombi that obliterate the vascular lumen and interrupt tissue perfusion. Likewise, irradiation impairs the function of osteoblasts, manifesting as osteopenia, with impairment of the repair and remodelling capacity of bone. Prior radiation exposure can thus decrease bone vascularity and injure its reserve reparative capacity. It is important to differentiate ORN from local recurrence of malignancy, bone metastasis, radiation-induced sarcoma, and infection. CT and MRI are effective diagnostic tools. Clinical management of ORN is complex and unsatisfactory. Treatment remains difficult, and prevention is paramount. A history of radiotherapy should alert clinicians to detect bone exposure or excessively prolonged socket healing. Early diagnosis with a high index of suspicion can achieve higher control rates with conservative management. Our case series reports a rare, previously unreported, but important complication of radiation therapy of the exenterated orbit.